2022
DOI: 10.3390/ijms23042214
|View full text |Cite
|
Sign up to set email alerts
|

Specific Gut Microbial Environment in Lard Diet-Induced Prostate Cancer Development and Progression

Abstract: Lard diet (LD) is a risk factor for prostate cancer (PCa) development and progression. Two immunocompetent mouse models fed with isocaloric specific fat diets (LD) enriched in saturated and monounsaturated fatty acid (SMFA), showed significanftly enhanced PCa progression with weight gain compared with a fish oil diet (FOD). High gut microbial divergency resulted from difference in diets, and the abundance of several bacterial species, such as in the orders Clostridiales and Lactobacillales, was markedly altere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The PCa level is closely related to age ( 22 ), levels of androgens ( 23 ), genetics ( 24 ) and obesity ( 25 ). Increasing evidence suggests obesity to be associated with an increased incidence of aggressive PCa ( 9 , 10 , 26 - 30 ) as well as an increased risk of biochemical failure following radical prostatectomy ( 31 ) and external-beam radiotherapy ( 32 ), Such results may be associated with a higher prevalence of complications following androgen-deprivation therapy, increased PCa-specific mortality, and difficulties in the treatment of obese men. Obesity may have an impact on the development and progression of PCa by influencing levels of adipokines ( 33 ), testosterone ( 23 ), and systemic inflammation ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The PCa level is closely related to age ( 22 ), levels of androgens ( 23 ), genetics ( 24 ) and obesity ( 25 ). Increasing evidence suggests obesity to be associated with an increased incidence of aggressive PCa ( 9 , 10 , 26 - 30 ) as well as an increased risk of biochemical failure following radical prostatectomy ( 31 ) and external-beam radiotherapy ( 32 ), Such results may be associated with a higher prevalence of complications following androgen-deprivation therapy, increased PCa-specific mortality, and difficulties in the treatment of obese men. Obesity may have an impact on the development and progression of PCa by influencing levels of adipokines ( 33 ), testosterone ( 23 ), and systemic inflammation ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when FMT containing CRPC feces was injected into mice, it was found that the expression of DNA-PKcs, RAD51, and LPCAT1 in the prostate tissue of mice was positively correlated with the malignant degree of PCa ( 60 ). Sphingosine 1-phosphate receptor 2 ( S1PR2 ) is a gene mainly regulated by a HFD, which is associated with abundantbody mass index, Lactobacillus, a low BMI and aggressive characteristics in patients with PCa ( 110 ). Additionally, S1PR2 expression is seen in host endothelial cells and tumor-infiltrating bone marrow cells, where it suppresses the expression of vascular endothelial growth factor and matrix metalloproteinase-9 activity to prevent tumor angiogenesis and tumor growth ( 111 ).…”
Section: Pathways Of Action Of the Gut Microbiota On Pcamentioning
confidence: 99%
“…Fexofenadine, a histamine H1 receptor antagonist, significantly reduced the proliferation of Pca cells in HFD-fed mice by suppressing the IL6/STAT3 signaling pathway (58). There were also differences in the composition and diversity of gut microbiota in mice fed with different components of HFD, such as lard and fish oil diets, and it was revealed that a diet rich in saturated fatty acids could lead to the progression of Pca and change the abundance of gut microbiota (59). The gut microbiota dysbiosis caused by HFD leads to Pca progression through multiple pathways, which further supports the existence of the gut microbiota-prostate axis.…”
Section: Pca and Gut Microbiome (Indirect)mentioning
confidence: 99%